Quality of Maternity Care and Client Satisfaction - Bhattarai, Saraswoti Kumari Gautam; Gautam, Kanchan (Journal of Karnali Academy of Health Sciences, 2019)
Health service provided to pregnant women during antenatal, childbirth and postnatal period is essential for maternal and child health. Proper care during pregnancy, childbirth and postnatal period are important for the health of mother and baby. High maternal, infant and child morbidity and mortality demand improved healthcare which does not concern to coverage of health services alone. The health issues of pregnant women, mothers, infants and children need to be addressed with the attention to the quality of care (QoC). The Nepal Health Sector Strategy (NHSS) also identifies equity and quality of care gaps as areas of concern for achieving the maternal health sustainable development goal (SDG) target. So this review aims to sensitize and draw attention to the quality of maternity care and client satisfaction to improve maternal and child health. For this article, different studies related to the quality of maternity care and satisfaction from care service received on maternity care are reviewed.